Penentuan Kapasitas PMT SF6 Pada Bus 70 KV Menggunakan Simulasi Program ETAP - Jeri Widianto; Rahmat Hidayat; Arief Budi Laksono (Universitas Islam Lamongan, 2021)
The electric power system consists of several components, namely generation, distribution, transmission and load. Along with the rapid development of technology in the field of electricity today, a protection system is installed at substations, one of which is a powerbreaker (PMT) at each substation. In the event of a disturbance, the protection relay will detect and instruct the breaker to open or disconnect the circuit from the disturbance, then a circuit breaker will receive a signal from the relay and in the end will decide the circuit according toits current rating. Based on the type of PMT isolation media, PMT is divided into 4 types, one of which is the SF6 gas isolation media type. This type of PMT can be used to cut currents up to 40 KA and in circuits with a voltage of 765 KV. It must be noted that if the current is very large at the time of short circuit, then the thing that must be considered is the capacity of thebreaker itself. To determine the breaker capacity, it is sought from the largest short-circuit current, namely a three-phase short circuit. In finding a three-phase short circuit current can be simulated using the ETAP (Electric Transient Analysis Program) program. ETAP can simulatepower flow and short circuit current. The results of the calculation of the PMT capacity on the 70 KV bus are 0.324 KA and from the results of the calculation and analysis of the PMT it is included in the rating of 12.5 KA where the PMT with the rating value can decide the fault current from 0.9 KA -7.74 KA